Pengaruh Sertifikasi Produk Terhadap Keputusan Pembelian dengan Persepsi Kualitas dan Kepercayaan Konsumen Sebagai Variabel Mediasi pada CV. Adi Jaya Mandiri - Ahmad Azhari Dwiputra; Aang Curatman; Dedi Muhammad Siddiq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The study employed a quantitative approach with a causal-comparative design through a cross-sectional survey. A sample of 107 CV. Adi Jaya Mandiri customers was selected using a purposive sampling technique. Data were collected using an online questionnaire with a 5-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The PLS-SEM results indicate that: Product certification has a direct positive and significant effect on purchasing decisions (β=0.343, p<0.05). Product certification also directly increases perceived quality (β=0.632, p<0.05) and consumer trust (β=0.641, p<0.05). Perceived quality (β=0.363, p<0.05) and consumer trust (β=0.279, p<0.05) have a positive effect on purchasing decisions. Perceived quality and consumer trust are shown to act as partial mediators in the relationship between product certification and purchasing decisions, with significant indirect mediation effects (β=0.229 and β=0.179, respectively, p<0.05). The research model has excellent predictive power with an R² value of 0.746 for the purchasing decision variable. Product certification is a crucial factor that not only directly drives purchasing decisions but also indirectly by improving perceived quality and building consumer trust. For CV. Adi Jaya Mandiri, proactive communication regarding certification, consistent product quality, and operational transparency are key to maximizing the positive impact of certification on consumer purchasing behavior.